PENGARUH PEMBERIAN BIOCHAR TERHADAP KETERSEDIAAN HARA N, P, K DAN PERTUMBUHAN TANAMAN JAGUNG DI TANAH GAMBUT - Pratama, Bisma Widya; Hayati, Rita; Agustine, Leony (Agros Journal of Agriculture Science, 2024)
Corn (Zea mays L.) is an important commodity in West Kalimantan as a second food commodity after rice as a carbohydrate. Peat soils that are easily leached result in low availability of nutrients in the soil. This study aims to determine the effect of giving biochar from corn cobs and rice husk biochar on the availability of N, P, and K nutrients, as well as the growth of corn plants in peat soils. This study used a Randomized Block Design (RAK) with 8 treatments, namely without corn cob biochar (J0), corn cob biochar 500 g/plot equivalent to 5 tons/ha (J1), corn cob biochar 1000 g/plot equivalent to 10 tons/ha (J2), corn cob biochar 1500 g/plot equivalent 15 tons/ha (J3), without rice husk biochar (S0), rice husk biochar 500 g/plot equivalent 5 tons/ha (S1), rice husk biochar 1000 g/plot equivalent to 10 tons/ha (S2), rice husk biochar 1500 g/equivalent plot 15 tons/ha (S3) with 4 replications and each plot consists of 8 plants, so that there are 32 experimental plots. The results show that the application of various doses of corncob biochar and rice husk biochar did not show a significant effect on soil pH, total soil N, soil available P, soil exchangeable K, plant height, and stem diameter.